Advantage in diversity: 9th grade pupils of mixed origin in Portugal - Mateus, S. (Portuguese Journal of Social Science, 2019)
This article focuses on a specific segment of children of immigrants: those of mixed origin, with one foreign parent and one native parent, protagonists of the plural and complex identities of contemporaneity. This group receives less attention in both the Portuguese and the international literature on migration, education and youth sociology; however, the group reveals distinctive singularities of social profiles, conditions, objective and subjective trajectories and future orientations. The discussion is based on data from a mixed-method research project involving 1,194 9th grade pupils aged 14–19 years in Portugal, including 405 children of immigrants, with 95 of mixed Portuguese/foreign origin. The comparative analysis reveals a insightful picture of the diverse characteristics and paths within the group of children of immigrants and confirms that mixed origin students encounter more favourable conditions and experiences, especially when compared with other students with immigrant backgrounds.